Primary bladder diffuse large B-cell lymphoma: a rare case report and literature review - Li, Ya; Hu, Xianwen; Cai, Jiong (Frontiers in Medicine, 2025)
Primary bladder diffuse large B-cell lymphoma (PB-DLBCL) is an exceedingly rare form of non-Hodgkin lymphoma, accounting for only 0.2% of all extranodal lymphomas. Here we report a case of PB-DLBCL in a woman presenting with hematuria. To determine the disease stage, an 18F-FDG PET/CT scan was performed after surgery. However, intense physiological 18F-FDG activity within the bladder lumen obscured potential lesions and concurrent CT imaging revealed suboptimal bladder distension limiting anatomical delineation. To address these limitations, 20 mg of intravenous furosemide was administered. Delayed imaging was performed 2 h after 18F-FDG injection (1 h after diuretic administration), revealing a focal hypermetabolic lesion in the left bladder wall. This metabolic pattern confirmed the diagnosis of PB-DLBCL, staged as IE according to the Ann Arbor classification. Following 4 cycles of R-CHOP chemotherapy, an 18F-FDG PET/CT scan was performed for treatment response assessment, confirming complete metabolic remission of the PB-DLBCL. This case highlights that dual-phase 18F-FDG PET/CT with intravenous diuretics can reduce bladder background activity and improve lesion visualization. Moreover, this approach holds significant clinical value in assisting with disease staging and evaluating treatment response.